PENERAPAN MEDIA AUDIO VISUAL UNTUK MENGENALKAN NILAI AKHLAK PADA ANAK DI TK AL-HIDAYAH ACEH SELATAN - Muthmainnah Ismail; Heliati Fajriah; Firiza Humaira (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
The introduction of moral values is a form of human development to become a human figure who is devoted to Allah SWT. Moral development must start early to form good character in children. Based on the observations of children in TK Al-Hidayah, children have not been able to distinguish between good values because of the limited use of media at that school. At that level, children should be familiar with honesty, politeness, respect, caring, and helping each other. This study aims to introduce moral values by using audio-visual media. This experimental research used a one group pretest-posttest design on 15 children of Al-Hidayah Kindergarten. Data collection uses a test to see the child's ability to recognize moral values through the animated films Nusa and Rara. The results showed that children began to recognize moral values before using audio-visual media with an average of 1.6. But after seeing the animation, the average value is 3.2 (Already Familiar). Then the t test obtained a t_count value of 23.98 and a t_table value of 1.761 with 14 degrees of freedom (db) at a significant level of 5% (0.05) and the difference in pretest and posttest values was 1.6. Based on data analysis, it can be said that t_count > t_table so that Ha is accepted and Ho is rejected. So it can be concluded that the application of audio-visual media can introduce children's moral values in Al-Hidayah Kindergarten, Samadua District, South Aceh Regency.